Synthesis, morphology, and compactibility of tetragonal zirconia nanopowders - Gabelkov, S.V.; Tarasov, R.V.; Poltavsev, N.S.; Starolat, M.P.; Andrievskaya, N.F.; Mironova, A.G.; Ledovskaya, E.G.; Litvinenko, L.M.; Odeychuk, M.A.; Belkin, F.V. (Functional Materials, 2007)
Fine-grained powders of tetragonal zirconia have been obtained by joint precipitation from aqueous zirconium and yttrium nitrate solutions followed by synthesis under thermal decomposition of hydroxides. The powders show three ordering levels, namely, conglomerates, agglomerates, and "primary" particles. The powder consists mainly of large ellipsoidal conglomerates of 1.5 to 2 μM size, the smaller agglomerates of 0.5 to 1 μM size and mostly irregular shape forming the minor fraction. Both conglomerates and agglomerates consist of rounded or irregular "primary" particles of 30 to 60 nm size. The studied tetragonal zirconia powders show a good compactibility providing the attainable high relative density (48 %) under a reasonable compacting pressure (256 MPa).